Costume design in New Zealand : designers and their design process : a thesis submitted for the degree of Master of Design at Massey University - Geus, Anne Margaret de (Massey University, 2006)
One of the aims of this research was to increase the knowledge base in the study and practice of costume design in New Zealand theatre through an investigation into the design processes and the working relationships of the costume designer and the director. The aim was to find a model for the design process used by the costume designer that is indicative of New Zealand. Is there evidence for a New Zealand aesthetic and do political, social and cultural influences affect the design process? As performance theatre ultimately depends on collaboration, the significance of the working relationships between the director and costume designer were explored. The primary source of data was semi-structured interviews involving ten costume designers and directors currently working within the theatre industry. These case studies provided data that were divided into categories, reflected on and then analysed. Comparisons were made between the published literature and oral data in order to discover the similarities, disparities, and connections in the perceptions of costume design and the processes involved in its creation. Key steps have been identified within the collaboration of director and costume designer that have formed a model for the design process that may be used in the production of a performance. The researcher has identified three categories; Preparation, Production and Evaluation. In the aesthetic of costume design for theatre, interviewees considered it inappropriate to show strong styling, as the vision generated from the script and design team is primary. Interviews suggested traits which are considered 'Kiwi' are more a flavour than a design styling and appear in approach, not aesthetics. Results of the interviews suggest that the theatre community in New Zealand is maturing, albeit it is conscious of the need for an adequate management and communication infrastructure in the light of the current economic situation facing the performing arts. Although technical skills needed to produce costumes are an asset, costume design is frequently combined with set design and the ability to communicate ideas is regarded as being of higher value.
Keywords: Costume design, New Zealand; Costume designers